Abondance et diversité des lichens au Nunavik en contexte de changements climatiques - Chagnon, Catherine (Université Laval, 2020)
Lichens are a key component of arctic and subarctic ecosystems, as they constitute an important part of biodiversity and are involved in many ecological processes. However, lichens appear vulnerable in the present context of climate change because of their poikilohydric metabolism and their slow growth rate. In order to understand the implications of climate change on lichens, we identified patterns and determinants of lichen abundance and diversity along a latitudinal gradient in Nunavik and evaluated the impact of shrubs on lichen communities. Our results reveal that vegetation types, which influence competitive interactions, and latitude, which is used as a proxy of regional climate, are the main factors involved in driving lichen abundance, diversity and community composition at the gradient scale. At the local scale, shrub and graminoid cover induces a lower lichen cover and diversity, highlighting the low competitive abilities of lichens. When comparing lichen communities in open area and under shrubs, we observe a decline of lichen cover of more than 50% under shrub canopy. Shrubs also induce a decline of lichen diversity that seems to intensify with time, and modify community composition by excluding species that require the open environment conditions. By combining two distinct methods, we highlighted the predominance of vascular plants in profiling lichen communities. As climate change is promoting further shrub expansion and a northward shift of vegetation zones, a major restructuration of lichen communities is likely to be observed in the next decades. By identifying environmental drivers of lichen communities at different spatial scales, this project takes part in a global effort towards a better understanding of northern ecosystems dynamics that aims to improve our ability to predict future changes in vegetation. Les lichens constituent une composante importante de la biodiversité en milieu arctique et subarctique et y jouent plusieurs rôles écologiques. En raison de leur métabolisme ...